2021
DOI: 10.1155/2021/9959320
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Potentials of Incretin‐Based Medications: A Review of Molecular Mechanisms

Abstract: Glucagon-like peptide 1 receptor agonists and dipeptidyl-peptidase 4 inhibitors are medications used for managing diabetes, mimicking the metabolic effects of incretin hormones. Recent evidence suggests that these medications have antioxidative potentials in the diabetic milieu. The pathophysiology of most diabetic complications involves oxidative stress. Therefore, if incretin-based antidiabetic medications can alleviate the free radicals involved in oxidative stress, they can potentially provide further ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…[2][3][4][5][6][7][8] Since their introduction, several different formulations of these antidiabetic agents have been brought to market; to date, seven injectable analogues (twicedaily exenatide immediate-release, once-weekly exenatide extendedrelease, once-daily liraglutide, once-daily lixisenatide, once-weekly albiglutide [currently off-market due to a decline in sales], onceweekly dulaglutide and once-weekly semaglutide) and one orallyadministered analogue (once-daily semaglutide) have been approved by the Food and Drug Administration (FDA). 9 Besides GLP-1 receptor as their putative target, numerous molecular targets have been identified for GLP-1 RAs, [10][11][12][13][14][15][16][17][18][19] which justifies their potential for wider medical applications. In this context, several studies have demonstrated that GLP-1 RAs can alter serum uric acid (SUA) concentration.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Since their introduction, several different formulations of these antidiabetic agents have been brought to market; to date, seven injectable analogues (twicedaily exenatide immediate-release, once-weekly exenatide extendedrelease, once-daily liraglutide, once-daily lixisenatide, once-weekly albiglutide [currently off-market due to a decline in sales], onceweekly dulaglutide and once-weekly semaglutide) and one orallyadministered analogue (once-daily semaglutide) have been approved by the Food and Drug Administration (FDA). 9 Besides GLP-1 receptor as their putative target, numerous molecular targets have been identified for GLP-1 RAs, [10][11][12][13][14][15][16][17][18][19] which justifies their potential for wider medical applications. In this context, several studies have demonstrated that GLP-1 RAs can alter serum uric acid (SUA) concentration.…”
mentioning
confidence: 99%
“…For instance, by reducing the generation of ROS, metformin therapy lowers blood glucose levels and oxidative stress [25]. By increasing antioxidant enzymes and lowering inflammatory cytokine levels, incretinbased treatments (e.g., glucagon-like peptide-1 (GLP-1) or dipeptidyl peptidase-4 (DPP-4) inhibitors) have shown antioxidative effects [83]. Exercise has been regularly proven to increase antioxidant capacity, decrease ROS production, and enhance cellular insulin sensitivity [84].…”
Section: Diabetes Therapy and Oxidative Stressmentioning
confidence: 99%
“…GLP-1 mimetics have varying abilities to protect against lipid peroxidation [ 80 ]. These drugs have potent direct and indirect antioxidative capacities (such as antioxidant defense system (ADS) potentiation, prooxidant inhibition, steroid receptor coactivator (SRC) protein suppression, and improvement in mitochondrial function) that enable them to prevent oxidative stress-induced lipid peroxidation [ 21 ]. Patel and colleagues in 2013 reported that GLP-1 therapy prevented lipid peroxidation via improving oxidative stress in mice [ 80 ].…”
Section: Incretins and Lipid Homeostasismentioning
confidence: 99%